Consumer's perception on the quality of controversial contents in edible bird's nest products - Mohamad Shukri, Nurul Nabilah Huda; Mohd Nawi, Nolila; Abdullah, Amin Mahir; Man, Norsida (Universiti Putra Malaysia Press, 2018)
Edible bird’s nest (EBN) originates from South East Asia and has become the most popular food delicacy among Chinese people. The price for raw and clean EBN are around RM 4,000 and RM 8,000 per kg, respectively. Due to the high market value of EBN and low maintenance cost, people ventures and invest in bird’s nest industry. The nesting house resembles the cave is built to attract swiftlets to roost and nest in it in order to meet the world’s growing demand. Out of the blue, in 2011, the EBN’s price falls half from its original price from RM 4,000 to RM 2,000. Nitrate found in raw or unclean EBN is one of the reason price plunges and the public also worried about counterfeit EBN that made from unclear substances. Thus, this review paper aims to highlight the nutritional properties in EBN that give medicinal benefits to consumers and the adulterant in EBN to increase the property contents with the dangerous mechanism by some irresponsible producers to obtain better profit which can threatening public’s health. In relation, these matters may influence consumer’s perception on EBN contents that could harm this industry. For that reason, scientific studies determined ways of handling EBN from scratch and distinguished the adulterant in EBN to reduce consumer anxiety was also discussed. Strict standard operation procedure enforces by the Malaysian Ministry of Health to farmers and producers are required, so that Malaysia EBN would appeal to the China market. Latter it can yield a good result and the price of EBN will slowly increase.